Eating behavior of Ongole crossbred and Limousin crossbred steers fed fermented rice straw and concentrate - Agung Purnomoadi; Agustina Wonga Bela; Sularno Dartosukarno (Jurnal Ilmu Ternak dan Veteriner, 2003)
A study on eating behavior of Ongole Crossbred (OC) and Limousin Crossbred (LC) steers (aged 9 months) fed fermented rice straw and concentrate has been carried out. Rice straw and concentrate were given in 60:40 ratio. Rice straw was fermented by commercial starter (BioP 2000 Z), while concentrate was composed of commercial concentrate and soybean pulp (by-product of soy-sauce industry). The diet was set to meet the dry matter (DM) requirement at 3.0% of liveweight. Eating behaviour was measured from 3 days continuously observation. Chewing number was accounted by halter equipped with tape-switch in jaw side and was recorded every 1/10 second in connected PC. The results showed that DMI of both OC (3.21 kg) and LC (4.18 kg) was similar, being 2.8% LW. However, chewing number of OC (133808 chews/d) was higher than that of LC (106353 chews/d). Chewing for eating and for rumination in OC (86995 and 46813 chews) was higher than of LC (67628 and 38725 chews). Chewing efficiency for eating in OC (0.041 g DMI/chew) was lower than that of LC (0.066 g DMI/chew). Similar tendency was observed in chewing efficiency for rumination that OC (0.080 g DMI/chew) was lower than that of LC (0.109 g DMI/chew). The conclusion is LC has a better chewing efficiency than of OC and it was pointed to different jaw size between OC and LC.   Key words: Chewing, Ongole, Limousin